The Development of the School of Spatial Analysis of W.Isard on the Basis of Economic and Supply Chain Management Models of the Petrochemical and Chemical Production Cluster - I.L. Beilin; V.V Homenko; D.D Aleeva (International Journal of Supply Chain Management, 2019)
Abstract- In the first post-war decade, studies of the problems of the regional economy were developed in many countries based on the supply chain management. Prerequisites were created for the unification of regional scientists and a new attempt to synthesize theories of spatial and regional economics. At this stage, the avant-garde role was played by an American scientist, W. Isard.Hi is first major monograph, â€œThe Placement and Economics of Space,â€ was published in which he posed the problem of eliminating the deep discrepancies that exist for more than 100 years between classical theories; accommodation and leading schools of general economic theory.W. Isard rightly criticizes all classical and neoclassical economic theories for the fact that they limited themselves to studying